2022
DOI: 10.7150/thno.73089
|View full text |Cite
|
Sign up to set email alerts
|

Integrated multi-omics characterization of KRAS mutant colorectal cancer

Abstract: KRAS mutation is the most frequent oncogenic aberration in colorectal cancer (CRC). The molecular mechanism and clinical implications of KRAS mutation in CRC remain unclear and show high heterogeneity within these tumors. Methods: We harnessed the multi-omics data (genomic, transcriptomic, proteomic, and phosphoproteomic etc.) of KRAS-mutant CRC tumors and performed unsupervised clustering to identify proteomics-based subgroups and molecular characterization. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…These mutations may activate other signaling pathways and increase tumor malignancy ( 13 ). Molecular subtyping based on proteomic and phosphoproteomic data ignores the influence of genetic background, simplifies tumor heterogeneity characterization, and provides potential biomarkers and therapeutic targets for each subtype with APC mutations ( 16 , 17 , 18 , 19 ). Molecular subtyping of APC -MUT colon cancer identifies a combination of molecular markers predicting prognosis in APC -MUT tumors, in which high expression of RAI14 in tumors is associated with poor prognosis in both WCH and CPTAC cohorts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These mutations may activate other signaling pathways and increase tumor malignancy ( 13 ). Molecular subtyping based on proteomic and phosphoproteomic data ignores the influence of genetic background, simplifies tumor heterogeneity characterization, and provides potential biomarkers and therapeutic targets for each subtype with APC mutations ( 16 , 17 , 18 , 19 ). Molecular subtyping of APC -MUT colon cancer identifies a combination of molecular markers predicting prognosis in APC -MUT tumors, in which high expression of RAI14 in tumors is associated with poor prognosis in both WCH and CPTAC cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of omics technologies and molecular classification methods has been widely used to help elucidate the heterogeneity of cancer ( 16 , 17 , 18 , 19 ). Inspired by these achievements, in this study, we carried out genomics of 76 pairs of colon cancer tissues and proteomics and phosphoproteomics analysis of 69 pairs of colon cancer tissues, of which 35 patients identified mutated APC s. Molecular classification based on the proteome and phosphoproteome data demonstrated the heterogeneity in APC -MUT tumors and identified RAI14 as a key prognostic marker.…”
mentioning
confidence: 99%
“…Further analyses have identified novel associations within pathways of amyloid pathology, neuronal injury, and tau hyperphosphorylation from the CSF of AD cases [147]. Similar analyses within oncology have identified molecular features associated with tumour invasiveness [148], immunotherapy susceptibility [149], and the subtypes of oncogene mutations [150]. Emerging methods are also supplementing unsupervised models with labelled datasets through semi-supervised learning to improve the identification of novel signatures.…”
Section: Unsupervised Machine Learning For Multiomicsmentioning
confidence: 93%
“…Herein, we summarize several features identified by multiomics studies. Based on integrated multiomics data, Chong et al reported that the KRAS-M1 (KM1) subtype was related to the CMS4 subtype, which, as opposed to the KRAS-M2 (KM2) subtype, is associated with a poor prognosis and increased angiogenesis, EMT, and TGF-β pathways 23 . Liu et al integrated drug sensitivity information and the phosphoproteome and reported that the combination of SHP2 and DOT1L inhibitors is an effective treatment for patients with subset 2 KRAS-mutant cancers 24 .…”
Section: Pathophysiology Of Crcmentioning
confidence: 99%